Dinamika Demografi dan Dampaknya Terhadap Pendapatan Asli Daerah Kota Batam - Wijanarko, Fadli; Ardieansyah, Ardieansyah (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to understand the relationship between demographic dynamics and the development of Local Original Income (PAD) in Batam City through a qualitative approach based on secondary data. Batam City has experienced significant population growth in recent years, influenced by high birth rates, massive in-migration, and low mortality rates. This growth has a direct impact on increasing economic activity and expanding the tax base and regional levies. The purpose of this study is to analyze how population growth, both in terms of quantity and structure, contributes to increasing PAD and how local governments respond to these changes through fiscal policy. The method used is a qualitative descriptive approach with analysis of secondary data trends from the Central Statistics Agency and the Batam City Government financial reports for the 2014–2023 period. The results of the study show a positive correlation between population growth and increasing PAD, especially from the trade, services, and industry sectors. However, population growth that is not balanced with transparent fiscal governance has the potential to put pressure on public services and infrastructure. Therefore, it is important for local governments to design adaptive and inclusive development strategies based on demographic data. In conclusion, population dynamics are an important factor in regional development that must be managed with responsive and evidence-based fiscal policies so that economic growth can be sustainable and equitable.